2016
DOI: 10.1037/tra0000137
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime trauma, personality traits, and health: A pathway to midlife health status.

Abstract: Objective This study investigated whether lifetime experience of trauma is related to personality through instrumental and reactive trait processes, and whether lifetime trauma is a mechanism underlying the association between childhood conscientiousness and objectively assessed adult physical health. Method Participants (N = 831) were 442 women and 389 men from the Hawaii longitudinal study of personality and health. Teacher assessments of personality were obtained when the participants were in elementary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
(63 reference statements)
1
6
0
Order By: Relevance
“…The retrospective measurement of trauma is vulnerable to biased reporting (e.g., Hepp et al, ); therefore, we analyzed trauma reports residualized with respect to vulnerability, the facet of adult Neuroticism most highly correlated with trauma reporting in this sample. We found evidence for both instrumental and reactive processes in the Hawaii study (Hampson et al, ). Trauma experienced in adolescence and adulthood mediated the association between childhood Conscientiousness and objective health status at age 51.…”
Section: Life Span Trait Mechanismssupporting
confidence: 62%
“…The retrospective measurement of trauma is vulnerable to biased reporting (e.g., Hepp et al, ); therefore, we analyzed trauma reports residualized with respect to vulnerability, the facet of adult Neuroticism most highly correlated with trauma reporting in this sample. We found evidence for both instrumental and reactive processes in the Hawaii study (Hampson et al, ). Trauma experienced in adolescence and adulthood mediated the association between childhood Conscientiousness and objective health status at age 51.…”
Section: Life Span Trait Mechanismssupporting
confidence: 62%
“…Regarding psychological outcomes, MHPs reported good overall mental health except for trait anxiety. In this context, previous research has shown that traumatic experiences can induce changes in trait variables [53], particularly in trait anxiety [54,55]. Thus, the high trait anxiety in our sample could be interpreted as an effect of the pandemic itself.…”
Section: Discussionmentioning
confidence: 56%
“… Gu et al (2013) conducted a national survey of law enforcement officers over six years and found that those who reported higher levels of psychological distress, likely related to exposure to traumatic events, were also heavier; when controlling for all potential confounders, this was true for women but not men. Hampson et al (2016) followed a community sample of children in Hawaii from childhood to adulthood and found that teen and adult trauma exposure was related to higher BMI and greater risk for obesity in adult women. In a longitudinal study of women nurses, Kubzansky et al (2014) found that women with at least four PTSD symptoms gained more weight than other women and were at increased risk for obesity.…”
Section: Introductionmentioning
confidence: 99%